Brief Research Report: How Do Claw Disorders Affect Activity, Body Weight, and Milk Yield of Multiparous Holstein Dairy Cows? - Magrin, Luisa; Cozzi, Giulio; Lora, Isabella; Prevedello, Paola; Gottardo, Flaviana (Frontiers in Veterinary Science, 2022)
Claw disorders are among the most relevant health problems in dairy herds. Despite being often not clearly visible and not easily detectable for farmers, they may appear as peculiar cow behavioral and performance patterns. This retrospective study aimed to assess cow’s behavior and production variations associated with claw disorders. The study involved 54 lactating Italian Holstein cows reared on the same dairy farm. A veterinarian performed the routine hoof trimming every 6 months, diagnosing specific claw disorders. Multiparous cows with no disorders at the first trimming were selected and monitored for the two following trimming sessions. Data coming from the automatic milking system and neck collars and related to the 15 days before a given cow was diagnosed with claw problems during trimming were furtherly collected. These data were compared with those recorded for the same animal over the 15 days preceding the previous trimming in which no claw disorders were observed. Compared to when they had no disorders, the cows affected by claw disorders had a lower daily activity (405 vs. 429 ± 27.7 units/d; P<0.001), showing a constant decrease in the last 10 days before the trimming, a lower milk yield (26.5 vs. 28.4 ± 1.57 kg/d; P=0.03), and only a decreasing trend of rumination time. These patterns of activity, milk yield, and rumination characterizing cows affected by claw disorders should promote the development of specific algorithms that would enable early detection of lameness thanks to the deviations of these parameters that are sensitive to cow claw health.